Conceptual model of persuasive multimedia content (PMC) for social media advertising of island homestays - Muhammad Abdul Malik, Saedon (2019)
This study encompasses the development and application of a conceptual model for social media advertising of island homestays. Findings through observation and two preliminary studies found that the use of advertising without suitable models, approaches, or strategies could lead the homestay industry into failure in terms of attracting potential customers. It is because relying on traditional advertising alone is no longer adequate. The majority of homestay operators were lack of advertising and promotion strategies. Thus, they wished to endeavor alternative strategy of advertising that can help them to improve their income performance. They believed that advertising through social media is a useful way to transform business by engaging with customers. Hence, this study proposes a conceptual model that embedded persuasive multimedia content (PMC) into advertisement. The main aim of this study is development of a conceptual model of PMC for social media advertising of island homestays. This is supported by four sub-objectives: (i) identification of the suitable components and elements for the conceptual model, (ii) development of the conceptual model of PMC, (iii) validation of the proposed conceptual model through expert review and prototyping, and (iv) measurement of the effectiveness of the prototype. The identified components and elements of the PMC were inserted into a diagram to form a conceptual model. Then, the conceptual model went through two validation processes by seven expert reviewers. For advertisement content creation, the conceptual model was applied into the advertisement content of island homestays to produce persuasive advertisement. The prototype of island homestay advertisement was uploaded on the island homestay‟s Facebook page. Paper-based and online questionnaires were distributed to measure the effectiveness of the advertisement. The technique used was copy-testing where 169 Facebook users viewed the island homestay advertisements and gave their response through the questionnaires. The results of the analysis showed that the application of the PMC were significant in influencing social media users‟ attitude. Dimension of advertisement content effect and persuasive multimedia that was correlated with other four dimensions are (i) attitude toward advertised brand, (ii) awareness of persuasive intent, (iii) attitude toward advertisement, and (iv) purchase intention, significantly effective in influencing their attitude toward island homestays. This is because homestay advertisements have attracted respondents‟ attention and persuaded them. They had positive tendency to experience the lifestyle in island homestays.